A Comprehensive Study on the Chemical, Biological, and Environmental Factors Shaping the Medicinal Value of Euphorbia hirta - J. B. Reshmi; P. S. Abitha; P. C. Divya; S. Grace Victoria; V. N. Meena Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Developmental biology, population metrics and evolutionary lineage of the Oriental fruit fly (Bactrocera dorsalis) on custard apple (Annona squamosa L.) - Arjun Sulagitti; Biradar A.P.; Udikeri S.S.; Shivakumara K.T.; Keerthi M.C.; Divya C; Prakash H.T.; Venugopal C.K.; Guru Yedahalli (Phytoparasitica, 2026)

Pac-rophage: Teaching Macrophage Phagocytosis Through Game Play - Caroline Cvetkovic; Madison C Fanning; Ali Ansari; Trisha Patnaik; Shreya Gustafson; Divya Bendigeri; Adam P Williamson; Elise A Corbin (Biomedical Engineering Education, 2026)

Intraspecific Variation of Edwardsiella anguillarum From Non‐Anguillid Fish From Varied Geographic Origins - Abigail R. Armwood; Divya Rose; Geoffrey C. Waldbieser; Ethan Woodyard; Bradley M. Richardson; Esteban Soto; Cynthia B. Stine; Cynthia C. Ware; Paola Barato; Alvin C. Camus; Matt J. Griffin (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum is a gram‐negative bacterium, synonymous with previously described atypical, fish‐pathogenic Edwardsiella tarda . Originally described from eels in 2015, E. anguillarum is an important global fish pathogen, particularly in tilapia. This study describes intraspecific phenotypic and genotypic variability among 17 E. anguillarum isolates from non‐anguillid fish hosts and varied geographic origins. Isolates demonstrated similar biochemical characteristics, with slight variation in motility and hydrogen sulfide production. Genomic relatedness among isolates was analysed with repetitive extragenic palindromic sequence‐based PCR (rep‐PCR) and multilocus sequence analysis (MLSA). Rep‐PCR with the ERIC II primer set revealed two distinct genetic clusters, while amplification strategies utilising the GTG 5 , BOX or ERIC I&II primer sets yielded more uniform profiles. While rep‐PCR deemed the isolates largely clonal, MLSA schemes using reference genes from published Edwardsiella MLSA studies revealed E. anguillarum isolates formed five discrete phylogroups. A unique, ~91.5 kB plasmid was identified in Costa Rican and Colombian isolates, associated with conjugative and transposable elements, plasmid mobilisation, and adhesion; however, no plasmid mediated antibiotic resistance genes were identified. This study provides insight into genetic diversity among E. anguillarum isolates from different hosts and geographic regions, identifying an optimal MLSA scheme from previous reports applicable to E. anguillarum isolates.

Field and geochemical characteristics of the southwestern part of Sendra Ambaji Granitoid Belt, Rajasthan, India: Implication on its petro-tectonic evolution - Akanksha Joshi; C. Aditya; Divya Prakash; Shubhabrata Mukhopadhyay (Acta Geochimica, 2026)

Biophysical basis and morphological traits conferring resistance to yellow stem borer, Scirpophaga incertulas (walker) in land races of rice (Oryza sativa L.) - Divya D. Mallesh; Vijaykumar Lingaraj; B. Shivanna; Reddy C. N. Lakshminarayana; M. S. Kitturmath; H. R. Raveendra; K. R. Ashoka (International Journal of Tropical Insect Science, 2026)

Stomatal and leaf hydraulic conductivity responses to changing light and CO2 conditions in Phaseolus vulgaris - Andrew Ogolla Egesa; Divya Rana; Jessica Barrera-Solis; William M. Hammond; C. Eduardo Vallejos; Kevin Begcy (Plant Science, 2026)

GC–MS phytochemical screening, molecular docking, MD simulation, and in vitro antioxidant assay of Euphorbia thymifolia L. extract - Nina Bhagyanath; Pushpaveni C.; Monica Arora; G. Divya Theja; Shithin Ann Varghese (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

Wild species Oryza rufipogon as a potential donor for development of interspecific backcross population in the background of Samba Mahsuri (BPT5204) and detection of yield enhancing QTLs - M. Sridhar; C. Gireesh; Divya Balakrishnan; M. Sujatha; M. S. Anantha; C. H. Raveendra; P. Senguttuvel; D. Srinivasa Chary; V. P. Bhadana; R. M. Sundaram (Plant Physiology Reports, 2025)

Genetic Diversity and Population Structure Analysis in Avocado (Persea americana) Accessions of India - B. M. Muralidhara; T. Sakthivel; D. C. Lakshmana Reddy; G. Karunakaran; V. Venkatravanappa; Siddanna Savadi; Divya Vani Vaka; Ponnam Naresh; K. S. Shivashankara; R. Venugopalan; M. K. Honnabyraiah (Agricultural Research, 2025)

From sea to cell: Investigating the potential health impacts of marine plastic pollution in the Philippines - Jasmine Santos; Beatrice Schleupner; Sophia Vincoff; Divya Dayanidhi; Ricardo Alindayu; Meagan M. Dunphy-Daly; William C. Eward; Jason A. Somarelli (Marine Pollution Bulletin, 2025)

Multi-environmental and multi-trait evaluation of elite finger millet genotypes for blast resistance using GGE biplot and stability analysis - Farooqkhan; K.B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H.R. Raveendra; T.S.S.K. Patro; Divya Bhandhari; Gandikota Brahmani; Prahlad Netam; Sujatha Bhat; H.E. Patil; Shaik Abdul Salam; et al. (Physiological and Molecular Plant Pathology, 2025)

Assessment of genetic diversity and haplotype analysis of Aphis nerii (Hemiptera: Aphididae) infesting on Gymnema sylvestre in India: Insights for sustainable crop production - Shivakumara KT; Divya C; Polaiah AC; Keerthi MC; Udikeri SS; Manjunatha C; Selva Babu (Phytoparasitica, 2025)

Comparative fitness of oleander aphid, Aphis nerii Boyer de fonscolombe (Hemiptera: Aphididae) on selected medicinal hosts using an age-stage, two-sex life table - K. T. Shivakumara; M. C. Keerthi; A. C. Polaiah; S. S. Udikeri; C. Divya; K. Swapnarani (International Journal of Tropical Insect Science, 2025)

Deciphering mating type and population genetic landscape of Magnaporthe population adapted to millets and rice in blast hotspots of India - K. B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H. D. Vinaykumar; Divya Bhandhari; H. R. Raveendra; T. S. S. K. Patro; T. V. Krishna; T. E. Nagaraja; R. Madhusudhana; C. Tara Satyavathi (Archives of Microbiology, 2025)

Marker Assisted Introgression and Evaluation of Retinol Equivalent Carotenoid in the Elite Cultivars Background from Traditional Landrace ‘Kavuni’ - Suvarna Rani Chimmili; G. Subashini; M. Raveendran; C. R. Anandakumar; Jyothi Badri; Divya Balakrishnan; S. Robin (Agricultural Research, 2025)

Component identification of solid biomass fuels using reflected light microscopy: Interlaboratory study 2 - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Menandro N. Acda; Tushar Adsul; Neža Malenšek Andolšek; Lorenzo Animali; Omid H. Ardakani; Telma Ataide; Demberelsuren Batbold; Mohd Younus Bhat; et al. (International Journal of Coal Geology, 2025)

Quercus leucotrichophora strategies to adapt the different environments in Western Himalaya - Pooja Negi; Deep C. Tiwari; Monika Rawat; Shinny Thakur; Divya Khatri; Rajiv Pandey; I. D. Bhatt; Sunil Nautiyal (Plant Ecology, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Cloud Computing Network in Remote Sensing-Based Climate Detection Using Machine Learning Algorithms - Jhade Srinivas; Ch VV Narasimha Raju; C. Sasikala; Parumanchala Bhaskar; Amarendra Reddy Panyala; Divya Priya (Remote Sensing in Earth Systems Sciences, 2025)

Physiological traits and population dynamics of Schizothorax niger (Heckel, 1838): Insights from Dal Lake and the Jhelum River, Kashmir, Himalayan region - Narayanan Karthik; Farooz Ahmad Bhat; Imtiyaz Qayoom; N. Jayakumar; C. Sudhan; P. Seenivasan; Divya Meril; Ishrat Mohd; Asra Mattoo (Journal of Fish Biology, 2025)
This study examines the physicochemical characteristics, morphometric features, biometric growth parameters, biological indices, physiological parameters, and biochemical profiles of Schizothorax niger population. The physicochemical analysis revealed a maximum temperature of 12.93 ± 1.33°C and hardness of 156.53 ± 12.82 mg/L in Dal Lake, whereas the Jhelum River had a minimum level of 10.94 ± 1.12°C temperature and 128.31 ± 11.62 mg/L of hardness. Dal Lake had a neutral pH (7.5 ± 0.2) and lower dissolved oxygen (6.8 ± 0.4 mg/L) compared to the Jhelum River (pH 7.2 ± 0.3; dissolved oxygen 7.5 ± 0.5 mg/L). Morphometric analysis showed significant differences ( p b = 3.15) than the Jhelum River ( b = 2.98). Biological indices revealed gender‐based variations in the gonado‐somatic index (GSI) and hepato‐somatic index (HSI), with GSI being higher in Dal Lake (0.21 ± 0.02) and HSI in the Jhelum River (1.04 ± 0.09). Haematological and biochemical analyses showed significant differences in parameters such as haematocrit (Dal Lake: 29.2 ± 2.1%; the Jhelum River: 32.4 ± 1.8%), glucose (Dal Lake: 85.3 ± 5.4 mg/dL; the Jhelum River: 68.1 ± 4.2 mg/dL), and total protein (Dal Lake: 6.2 ± 0.4 g/dL; the Jhelum River: 5.8 ± 0.3 g/dL) between sites. These findings provide valuable insights into the physiological traits and population dynamics of S. niger , informing species‐specific conservation strategies and ecosystem management practices.

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Assessment of the calcium-silicate Polonite as a sorbent for thin-layer capping of metal contaminated sediment - Johan Wikström; Divya Pal; Roshan Prabhakar; Sara C. Forsberg; Agnieszka Renman; Jing Ai; Gunno Renman; Jonas S. Gunnarsson (Chemosphere, 2024)

Multi-environment testing revealed the effect of yield genes on the grain yield stability in diverse rice germplasm - Aleena Dasari; Divya Balakrishnan; Santosha Rathod; P. V. R. Rao; Laksminarayana R. Vemireddy; C. N. Neeraja; S. Vanisri; K. N. Ranjith; R. M. Sundaram; Jyothi Badri (Cereal Research Communications, 2024)

Identification of hub genes associated with stripe rust disease in wheat through integrative transcriptome and gene-based association study - Divya Chauhan; Dwijesh Chandra Mishra; Shikha Mittal; Sushma Rani; Jyotika Bhati; Sundeep Kumar; Subhash C. Bhardwaj; Monendra Grover; Neeraj Budhlakoti; Suphiya Khan (South African Journal of Botany, 2024)

Stability analysis and genetic mapping for yield traits of rice wild introgression lines - N. P. S. De Silva; P. Magudeeswari; Divya Balakrishnan; V. Gouri Shankar; B. Kavitha; A. Krishnamraju; P. Prashanthi; K. Vaibhav; D. S. Chary; S. N. C. V. L. Pushpavalli; Sarla Neelamraju (Cereal Research Communications, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Mapping QTLs for grain iron, zinc, and yield traits in advanced backcross inbred lines of Samba mahsuri (BPT5204)/Oryza rufipogon - Gowthami Chandu; Divya Balakrishnan; Suchandranath Babu Munnam; Satendra K. Mangrauthia; Durbha Sanjeeva Rao; C. N. Neeraja; R. M. Sundaram; Sarla Neelamraju (Journal of Plant Biochemistry and Biotechnology, 2024)

Low clouds over the subtropical Indian Ocean and sub-seasonal circulation associations with the Indian summer monsoon - T. Gokul; R. K. Vellore; D. C. Ayantika; V. Divya; R. Krishnan; M. J. K. Reji (Climate Dynamics, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Microbial distribution and diversity along a vertical profile in the water column of a seasonal Oxygen minimum zone in the Southeast Arabian Sea - Abdulaziz Anas; Balu Tharakan; Devika Raj K.; Jasmin C.; Baby Divya; Shijin Ameri; Saravanane Narayanan (Regional Studies in Marine Science, 2023)

Meta-QTL analysis in wheat: progress, challenges and opportunities - Divya Sharma; Anita Kumari; Priya Sharma; Anupma Singh; Anshu Sharma; Zahoor Ahmad Mir; Uttam Kumar; Sofora Jan; M. Parthiban; Reyazul Rouf Mir; Pradeep Bhati; Anjan Kumar Pradhan; et al. (Theoretical and Applied Genetics, 2023)

Interlaboratory study: Testing reproducibility of solid biofuels component identification using reflected light microscopy - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Tushar Adsul; Neža Malenšek Andolšek; Omid Haeri Ardakani; Tara Congo; Batbold Demberelsuren; Bryon S. Donohoe; Ashley Douds; Deolinda Flores; et al. (International Journal of Coal Geology, 2023)

Evaluation of Thermostable Biomolecule Cocktail from Algal-associated Hot Water Spring Bacteria for Antibiofilm Activities - Mubassira K. Shaikh; Divya D. Patel; Shraddha C. Dobariya; Anoop R. Markande (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Comparative transcriptome profiling of near isogenic lines PBW343 and FLW29 to unravel defense related genes and pathways contributing to stripe rust resistance in wheat - Zahoor Ahmad Mir; Divya Chauhan; Anjan Kumar Pradhan; Vivek Srivastava; Divya Sharma; Neeraj Budhlakoti; Dwijesh Chandra Mishra; Vasudha Jadon; Tanmaya Kumar Sahu; Monendra Grover; Om Prakash Gangwar; Subodh Kumar; et al. (Functional & Integrative Genomics, 2023)

Seasonal forecasting of tropical cyclones over the Bay of Bengal using a hybrid statistical/dynamical model - C. T. Sabeerali; O. P. Sreejith; Nachiketa Acharya; Divya E. Surendran; D. S. Pai (International Journal of Climatology, 2022)
The post‐monsoon (October–November–December) tropical cyclone (TC) over the Bay of Bengal is one of the most devastating natural disasters causing economic and human losses over India and its neighbouring countries. This study discusses a hybrid statistical/dynamical model developed to forecast the post‐monsoon cyclone activities over the Bay of Bengal, where 80% of the TCs of the North Indian Ocean are originated. In the hybrid model, the coupled model CFSv2 predicts the large‐scale climate indices, and the principal component regression (PCR) model is used to relate these indices with the TC frequency. A solid concurrent relation between the cyclonic disturbance frequencies and various large‐scale variables is noted. The dynamical variable, for example, the zonal wind, acts as a precursor variable. We identified three concurrent predictors (ocean heat content over the Bay of Bengal, sea surface temperature (SST) over the Indian Ocean, and SST over the tropical central Pacific regions) and two precursor predictors (low‐level wind at equatorial Indian ocean and strength of upper‐level easterly jet over African coast) influencing the cyclonic disturbance frequencies over the Bay of Bengal. The concurrent predictors are calculated from the CFSv2 hindcast/forecast output and the precursor predictors are calculated from the reanalysis data. The predictors influencing the cyclonic disturbance over the Bay of Bengal are also influencing the cyclonic storms. Hence, the same predictors are used for developing a hybrid model for cyclonic disturbance and storm frequencies. A significant inter‐correlation among different predictors is observed and the PCR model avoids these inter‐correlations and, in this method, PCs are estimated on the predictors to make them orthogonal to each other. The hybrid model achieved a significant skill for seasonal cyclone forecast over the Bay of Bengal. Results suggest the potential for using the hybrid model for the operational seasonal forecasting of post‐monsoon cyclone activity over the Bay of Bengal.

Activated Hollow and Solid Carbon Spheres for Enhanced Removal Efficiency of Pharmaceutical Pollutants and Heavy Metals in Water - Devika Laishram; Divya Kumar; Vishav Kant; Bhagirath Saini; Kiran P. Shejale; R. Krishnapriya; Vikash C. Janu; Rahul Singhal; Rakesh K. Sharma (Water, Air, & Soil Pollution, 2022)

Impact of environment and LULC changes on groundwater resources in the Soan Basin, western Himalaya - Divya Thakur; S. K. Bartarya; H. C. Nainwal; Som Dutt (Environmental Monitoring and Assessment, 2022)

A facile synthesis of CuBi2O4 hierarchical dumbbell-shaped nanorod cluster: a promising photocatalyst for the degradation of caffeic acid - Mohammad Ashfaq; Neetu Talreja; Divya Chauhan; C. A. Rodríguez; Adriana C. Mera; Mangalaraja Ramalinga Viswanathan (Environmental Science and Pollution Research, 2022)

Statolith chemistry: a new tool to understand the ecology and provenance of octopus - Divya S. Daryanani; Jasmin C. Martino; Zoë A. Doubleday (Reviews in Fish Biology and Fisheries, 2021)

Occurrence of the supposedly endemic Australian azooxanthellate coral Astrangia woodsi Wells, 1955 in the eastern Arabian Sea - Divya Viswambharan; K. R. Sreenath; S. Jasmine; K. K. Joshi; C. R. Sreeraj; Smruthu Mohan; Prathibha Rohit (Marine Biodiversity, 2021)

Acellular Scaffolds as Innovative Biomaterial Platforms for the Management of Diabetic Wounds - Vyshnavi Tallapaneni; C. Kalaivani; Divya Pamu; Lavanya Mude; Sachin Kumar Singh; Veera Venkata Satyanarayana Reddy Karri (Tissue Engineering and Regenerative Medicine, 2021)

Re-Description of Sillago malabarica, Silver Whiting from Southern Indian Waters - P. R. Divya; Rahul G. Kumar; Linu Joy; C. P. Rajool Shanis; V. S. Basheer; K. K. Lal (Thalassas: An International Journal of Marine Sciences, 2021)

Exploring the Diversity of the Marine Environment for New Anti-cancer Compounds - Divya L. Dayanidhi; Beatrice C. Thomas; Joshua S. Osterberg; Mallissa Vuong; Giselle Vargas; Sarah K. Kwartler; Emma Schmaltz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Daniel Rittschof; William C. Eward; Christopher Roy; et al. (Frontiers in Marine Science, 2021)
Marine ecosystems contain over 80% of the world’s biodiversity, and many of these organisms have evolved unique adaptations enabling survival in diverse and challenging environments. The biodiversity within the world’s oceans is a virtually untapped resource for the isolation and development of novel compounds, treatments, and solutions to combat human disease. In particular, while over half of our anti-cancer drugs are derived from natural sources, almost all of these are from terrestrial ecosystems. Yet, even from the limited analyses to date, a number of marine-derived anti-cancer compounds have been approved for clinical use, and several others are currently in clinical trials. Here, we review the current suite of marine-derived anti-cancer drugs, with a focus on how these compounds act upon the hallmarks of cancer. We highlight potential marine environments and species that could yield compounds with unique mechanisms. Continued exploration of marine environments, along with the characterization and screening of their inhabitants for unique bioactive chemicals, could prove fruitful in the hunt for novel anti-cancer therapies.

Leaf blast disease in finger millet [Eleusine coracana (L.) Gaertn.] caused by Bipolaris sorokiniana Sacc.: a histopathological study - Pereira Preethi; M. S. Sharada; C. R. Divya (Journal of Plant Diseases and Protection, 2020)

Head Impact Sensor Studies In Sports: A Systematic Review Of Exposure Confirmation Methods - Declan A. Patton; Colin M. Huber; Divya Jain; Rachel K. Myers; Catherine C. McDonald; Susan S. Margulies; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Deciphering demographic history and fine-scale population structure of cobia, Rachycentron canadum (Pisces: Rachycentridae) using microsatellite and mitochondrial markers - P. R. Divya; Joy Linu; C. Mohitha; A. Kathirvelpandian; P. Manoj; V. S. Basheer; A. Gopalakrishnan (Marine Biodiversity, 2019)

Caste-Specific Expression of Na+/K+-ATPase in the Asian Weaver Ant, Oecophylla smaragdina (Fabricius, 1775) - C C Sheeja; V V Thushara; L Divya (Neotropical Entomology, 2018)

Four evolutionarily significant units among narrow-barred Spanish mackerel (Scomberomorus commerson) in the Indo-West Pacific region - N Vineesh; PR Divya; A Kathirvelpandian; C Mohitha; CPR Shanis; VS Basheer; A Gopalakrishnan (Marine Biodiversity, 2018)

Development and Characterization of SSR Markers to Study Genetic Diversity and Population Structure of Horsegram Germplasm (Macrotyloma uniflorum) - R. K. Chahota; Divya Shikha; Maneet Rana; Vikas Sharma; Akshay Nag; T. R. Sharma; J. C. Rana; Hideki Hirakawa; Sachiko Isobe (Plant Molecular Biology Reporter, 2017)

Enhancement of the Oral Bioavailability of Felodipine Employing 8-Arm-Poly(Ethylene Glycol): In Vivo, In Vitro and In Silico Evaluation - Pius Fasinu; Yahya E. Choonara; Pradeep Kumar; Lisa C. du Toit; Divya Bijukumar; Riaz A. Khan; Viness Pillay (AAPS PharmSciTech, 2017)

Optimisation of Hidden Markov Model using Baum–Welch algorithm for prediction of maximum and minimum temperature over Indian Himalaya - J C JOSHI; TANKESHWAR KUMAR; SUNITA SRIVASTAVA; DIVYA SACHDEVA (Journal of Earth System Science, 2017)

Design of an Inflammation-Sensitive Polyelectrolyte-Based Topical Drug Delivery System for Arthritis - Divya Bijukumar; Yahya E. Choonara; Karmani Murugan; Bibi Fatima Choonara; Pradeep Kumar; Lisa C. du Toit; Viness Pillay (AAPS PharmSciTech, 2016)

Effects of zolpidem alone and in combination with nabilone on cannabis withdrawal and a laboratory model of relapse in cannabis users - Evan S. Herrmann; Ziva D. Cooper; Gillinder Bedi; Divya Ramesh; Stephanie C. Reed; Sandra D. Comer; Richard W. Foltin; Margaret Haney (Psychopharmacology, 2016)

PPIA rs6850: A > G single-nucleotide polymorphism is associated with raised plasma cyclophilin A levels in patients with coronary artery disease - A. Vinitha; V. Raman Kutty; A. Vivekanand; G. Reshmi; G. Divya; S. Sumi; K. R. Santosh; N. S. Pratapachandran; Mullassari S. Ajit; C. C. Kartha; Surya Ramachandran (Molecular and Cellular Biochemistry, 2016)

Characterization of microsatellite markers in silver pomfret, Pampus argenteus (Perciformes: Stromateidae) through cross-species amplification and population genetic applications - C. MOHITHA; LINU JOY; P. R. DIVYA; A. GOPALAKRISHNAN; V. S. BASHEER; MOHAMMED KOYA; J. K. JENA (Journal of Genetics, 2015)

Assessing the tolerance of immobilized laccase from a salt-tolerant strain of Trichoderma viride Pers NFCCI-2745 to heavy metal ions, detergents and copper chelating agents - L. M. Divya; G. K. Prasanth; C. Sadasivan (International Journal of Environmental Science and Technology, 2015)

Molecular phylogenetics of three species of the genus Rastrelliger using mitochondrial DNA markers - V. S. Basheer; C. Mohitha; N. Vineesh; P. R. Divya; A. Gopalakrishnan; J. K. Jena (Molecular Biology Reports, 2015)

Overexpression of EaDREB2 and pyramiding of EaDREB2 with the pea DNA helicase gene (PDH45) enhance drought and salinity tolerance in sugarcane (Saccharum spp. hybrid) - Sruthy Maria Augustine; J. Ashwin Narayan; Divya P. Syamaladevi; C. Appunu; M. Chakravarthi; V. Ravichandran; Narendra Tuteja; N. Subramonian (Plant Cell Reports, 2015)

Production, purification and characterization of cholesterol oxidase from a newly isolated Streptomyces sp. - Ram Niwas; Vineeta Singh; Rajbir Singh; Divya Tripathi; C. K. M. Tripathi (World Journal of Microbiology and Biotechnology, 2013)

Ethanol and Vitamin D Receptor in T Cell Apoptosis - Shabina Rehman; Nirupama Chandel; Divya Salhan; Partab Rai; Bipin Sharma; Tejinder Singh; Mohammad Husain; Ashwani Malhotra; Pravin C. Singhal (Journal of Neuroimmune Pharmacology, 2013)

Prevalence of Very Low Numbers of Potential Pathogenic Isolates of Yersinia enterocolitica and Yersinia intermedia in Traditional Fast Foods of India - K. H. Divya; M. C. Varadaraj (Indian Journal of Microbiology, 2011)

The Effect of Magnetic Field Dependent Viscosity on Thermosolutal Convection in a Ferromagnetic Fluid Saturating a Porous Medium - Sunil; Divya; R. C. Sharma (Transport in Porous Media, 2005)

Numerical simulation by a stretched-coordinate Ocean General Circulation Model: A preliminary results - Arun Chakraborty; H. C. Upadhyaya; O. P. Sharma; Divya Jaisawal; S. K. Deb (Meteorology and Atmospheric Physics, 2003)